EFFICIENCY OF DEEP FLUORIDATION IN PREVENTION OF ENAMEL CARIES - Zh. V. Solovyova; A. A. Adamchik (Кубанский научный медицинский вестник)
Aim. The purpose of the study is to evaluate the clinical effectiveness of the use of the domestic preparation for deep fluoridation "Fluor Lux" (TechnoDent, Russia) in prevention of enamel caries.Materials and methods. The clinical studies have been conducted on the basis of the Department of Therapeutic Dentistry and the Dental Polyclinic of the FSBEI HE KubSMU of the Ministry of Healthcare ofRussia. In total, 50 volunteers aged 20-30 with different levels of oral hygiene have taken part. To estimate the effi of remineralizing action with the preparation for deep fl "Fluor Lux", (TechnoDent), volunteers have undergone the enamel resistance test (ER-test) according to V.R. Okushko and the acid biopsy of the enamel according to the method of V.K. Leontiev and V.A. Distel. The comparison of the indices of the acid enamel biopsy and the enamel resistance test in the study groups has been carried out using the Student's test. Results. One of the determining factors for the effectiveness of the enamel remineralization is the adherence to the individual oral hygiene. The results of the acidic enamel biopsy and the enamel resistance test in the first group of patients with the hygiene level OHI-S = 0-1,67 have indicated the effectiveness of the use of the drug "Fluor Lux" remedy (TechnoDent, Russia) for deep fluoridation of the enamel in the caries prophylaxis program. In the second group of patients (insufficient and poor OHI-S levels = 1,7-3), in 3 months, no statistically significant changes in the estimated parameters have been detected. The level of total calcium (Ca2+) in the enamel biopsy samples has decreased, but these changes have been statistically insignificant (p>0,05). The content of the inorganic phosphonate (PO4)3unlike Ca2+ has significantly decreased in the enamel biopsy samples (p*<0,05). The changes in the ER-test have been statistically insignificant (p>0,05).Conclusion. Thus, the obtained results of the study make it possible to recommend the deep fluorination with the "Fluor lux" remedy (TechnoDent, Russia) in order to increase the effectiveness of prophylaxis of caries enamel. However, one of the determinants for the effectiveness of enamel remineralization is the adherence to the individual oral hygiene.